A β–glucuronosyltransferase from Arabidopsis thaliana involved in biosynthesis of type II arabinogalactan has a role in cell elongation during seedling growth. (29th November 2013) - Knoch, Eva; Dilokpimol, Adiphol; Tryfona, Theodora; Poulsen, Christian P.; Xiong, Guangyan; Harholt, Jesper; Petersen, Bent L.; Ulvskov, Peter; Hadi, Masood Z.; Kotake, Toshihisa; Tsumuraya, Yoichi; Pauly, Markus; et al.
Summary We have characterized a β–glucuronosyltransferase (AtGlcAT14A) from Arabidopsis thaliana that is involved in the biosynthesis of type II arabinogalactan (AG). This enzyme belongs to the Carbohydrate Active Enzyme database glycosyltransferase family 14 (GT14). The protein was localized to the Golgi apparatus when transiently expressed in Nicotiana benthamiana. The soluble catalytic domain expressed in Pichia pastoris transferred glucuronic acid (GlcA) to β–1, 6–galactooligosaccharides with degrees of polymerization (DP) ranging from 3–11, and to β–1, 3–galactooligosaccharides of DP5 and 7, indicating that the enzyme is a glucuronosyltransferase that modifies both the β–1, 6‐ and β–1, 3‐galactan present in type II AG. Two allelic T–DNA insertion mutant lines showed 20–35% enhanced cell elongation during seedling growth compared to wild‐type. Analyses of AG isolated from the mutants revealed a reduction of GlcA substitution on Gal–β–1, 6–Gal and β–1, 3–Gal, indicating an in vivo role of AtGlcAT14A in synthesis of those structures in type II AG. Moreover, a relative increase in the levels of 3‐, 6‐ and 3, 6‐linked galactose (Gal) and reduced levels of 3‐, 2‐ and 2, 5‐linked arabinose (Ara) were seen, suggesting that the mutation in AtGlcAT14A results in a relative increase of the longer and branched β–1, 3‐ and β–1, 6‐galactans. This increase of galactosylation in the mutants is most likely caused by increased availability of the O6 position of Gal, which is a shared acceptor site for AtGlcAT14A and galactosyltransferases in synthesis of type II AG, and thus addition of GlcA may terminate Gal chain extension. We discuss a role for the glucuronosyltransferase in the biosynthesis of type II AG, with a biological role during seedling growth.